2020
DOI: 10.1029/2020gl088990
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic Source Modeling of the 2019 Mw 6.3 Durrës, Albania, Earthquake: Partial Rupture of a Blind Reverse Fault

Abstract: We address geometric and kinematic properties of the M w 6.3 26 November 2019 Durrës earthquake, the strongest earthquake in Albania in the past 40 years. Using coseismic surface displacements from Sentinel-1 Differential Interferometric Synthetic Aperture Radar (DInSAR) and nearby Global Navigational Satellite System (GNSS) stations, we invert for the geometry and slip of the causative fault. We find that both a steep SW-dipping fault (dip 71°) and a shallow NE-dipping fault (dip 15°) can fit the data equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…We note that the compressional axis becomes notably larger compared to the corresponding extensional axis in the epicentral area of the 2019 M w 6.3 Durrës earthquake. At this region we resolve a NE‐SW oriented compression of 45 nstrain/yr, which is consistent with the NW‐SE trending reverse fault that ruptured during the 2019 mainshock (e.g., Govorčin et al., 2020; Pezzo et al., 2022). The other region where the strain rate field is dominated by compression lies in northwestern Greece and, more specifically, in western Epirus and Paxoi Islands.…”
Section: Quantification Of Geodetic Deformation Ratessupporting
confidence: 79%
“…We note that the compressional axis becomes notably larger compared to the corresponding extensional axis in the epicentral area of the 2019 M w 6.3 Durrës earthquake. At this region we resolve a NE‐SW oriented compression of 45 nstrain/yr, which is consistent with the NW‐SE trending reverse fault that ruptured during the 2019 mainshock (e.g., Govorčin et al., 2020; Pezzo et al., 2022). The other region where the strain rate field is dominated by compression lies in northwestern Greece and, more specifically, in western Epirus and Paxoi Islands.…”
Section: Quantification Of Geodetic Deformation Ratessupporting
confidence: 79%
“…Ganas et al (2020) and Vittori et al (2021) favour an E‐dipping fault, consistent with the activation of a deep‐blind‐low‐angle thrust. Govorčin et al (2020) discussed both geometries and supported the activation of a blind‐high‐angle back‐thrust, namely the Vore back‐thrust. The east‐dipping plane, with a great depth of 20 km and low dip angle, is not an obvious feature of the regional structural setting (see also Vittori et al, 2021), decoupled from the shallower east‐verging thrust system and poorly known or constrained.…”
Section: Discussionmentioning
confidence: 99%
“…This earthquake is part of a seismic sequence spreading from late 2019 to early 2020 with 8 M w > 5 reverse FMs with belt‐perpendicular P ‐axes. Due to a rather sparse aftershock distribution and absence of primary surface coseismic ruptures (Papadopoulos et al, 2020), previous studies modelled the mainshock as either a low‐angle ENE‐dipping thrust (Caporali et al, 2020, Ganas et al, 2020, Papadopoulos et al, 2020; Vittori et al, 2021) or a SW‐dipping back‐thrust (Govorčin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 6‐year period only covers a small portion of the long earthquake cycle, and our investigation focuses on a single tectonic region. Despite these possible limits, we believe the considerable moments released in the uppermost crust could be a general conclusion, based on the observations that more and more shallow earthquakes in other continents have been reported with InSAR data (e.g., Dawson et al., 2008; Govorčin et al., 2020; Materna et al., 2019; Motagh et al., 2015; Ritz et al., 2020; Wei et al., 2015). The findings in this study have shown the great potential of an InSAR‐based earthquake catalog.…”
Section: Discussionmentioning
confidence: 89%